The VirB4 ATPase of Agrobacterium tumefaciens is a cytoplasmic membrane protein exposed at the periplasmic surface. - Dang, T A (1997)
The VirB4 ATPase of Agrobacterium tumefaciens, a putative component of the T-complex transport apparatus, associates with the cytoplasmic membrane independently of other products of the Ti plasmid. VirB4 was resistant to extraction from membranes of wild-type strain A348 or a Ti-plasmidless strain expressing virB4 from an IncP replicon. To evaluate the membrane topology of VirB4, a nested deletion method was used to generate a high frequency of random fusions between virB4 and 'phoA, which encodes a periplasmically active alkaline phosphatase (AP) deleted of its signal sequence. VirB4::PhoA hybrid proteins exhibiting AP activity in Escherichia coli and A. tumefaciens had junction sites that mapped to two regions, between residues 58 and 84 (region 1) and between residues 450 and 514 (region 2). Conversely, VirB4::beta-galactosidase hybrid proteins with junction sites mapping to regions 1 and 2 exhibited low beta-galactosidase activities and hybrid proteins with junction sites elsewhere exhibited high beta-galactosidase activities. Enzymatically active VirB5::PhoA hybrid proteins had junction sites that were distributed throughout the length of the protein. Proteinase K treatment of A. tumefaciens spheroplasts resulted in the disappearance of the 87-kDa VirB4 protein and the concomitant appearance of two immunoreactive species of approximately 35 and approximately 45 kDa. Taken together, our data support a model in which VirB4 is topologically configured as an integral cytoplasmic membrane protein with two periplasmic domains.